(untitled) (Research, Society and Development, 2020)
The productive versatility of the facheiro associated with the natural availability of the species causes an exploration without planning. Consequently, few studies have been carried out on the conservation and maintenance of the species, mainly in the Northeast Region. The aim of the present study was to evaluate the effect of the simplified medium and the alternative gelling agent, corn starch, on the in vitro germination of Pilosocereus pachycladus. The seeds were disinfected and inoculated in a culture medium containing commercial fertilizers, supplemented with sucrose, and gelled with agar and corn starch. The treatments: complete salts of Calcinit® and Kristalon® and gelled with agar - CKAG; half of the Calcinit® and Kristalon® salts and gelled with agar - MCKAG; complete salts of Calcinit® and Kristalon® and gelled with corn starch - CKAM; half of the Calcinit® and Kristalon® salts and gelled with corn starch - MCKAM. The CKAG medium promoted a lower percentage of contamination by 20%. And the CKAM and MCKAM media obtained 67 and 75% for germination percentage, respectively. The highest averages for aerial part height were for the CKAM and CKAG media with 0.32 and 0.30 cm, respectively. And for the length of the root, the highest value was for the CKAG medium with 0.65 cm. There was no significant effect on seedling acclimatization for treatments. In view of the results obtained, it is suggested the use of corn starch in culture media as an excellent alternative for in vitro germination of the P. pachycladus, providing cost reduction and a satisfactory germination percentage.